“Urip Mung Mampir Ngguyu” :Tinjauan Falsafah Jawa dan Akhlak Humor - Robingun Suyud El Syam; Salis Irvan Fuadi; Ngatoillah Linnaja (Journal on Education, 2023)
Human nature tends to happiness and pleasure which is the driving force for the expression of laughter. The Al-Qur'an and Hadith discuss it a lot, medical facts also find a variety of benefits. It's a pity, laughing harms others. With a theoretical study, he concluded: "Urip Mung Mampir Ngguyu" in Javanese philosophy contains a moral message, living in the world is not a goal, the essence of the urgency is to serve God. From the point of view of the morality of humorous, laughter in life should be an expression of gratitude or good value, not exaggeration, ridicule or harm to others.